MANAJEMEN RISIKO KREDIT GUNA MEMINIMALISIR KREDIT BERMASALAH PADA PERUMDA BPR KABUPATEN MADIUN - Hery Hermawan; Fatchur Rochman; Retno Iswati (Universitas Merdeka Madiun, 2024)
Abstract— This study aims to determine the credit management carried out at Perumda BPR Madiun Regency in an effort to minimize non-performing loans, to find out what factors cause non-performing loans to Perumda BPR Madiun Regency. On the other hand, it is to find out the handling of non-performing loans at Perumda BPR Madiun Regency. This type of research is a descriptive research. Data obtained from primary data, namely data obtained from informants directly and secondary data in the form of documents or previous research. Data collection techniques namely interviews, observation and review of written documents. The results of the study show that credit management carried out at Perumda BPR Madiun Regency in an effort to minimize non-performing loans has been able to run effectively. This is because the implementation of credit management carried out at Perumda BPR Madiun Regency in an effort to minimize non-performing loans is in accordance with POJK No. 13/POJK.03/2015. As well as the factors that cause problem loans, namely internal factors originating from the Perumda BPR Madiun Regency and external factors originating from the debtor. In addition, the handling of non-performing loans at Perumda BPR Madiun Regency takes the form of rescheduling, reconditioning and restructuring.